2007
DOI: 10.1002/jez.b.21165
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hormone mediates sexual dimorphism in horned beetles

Abstract: The causes and consequences of sexual dimorphism are major themes in biology. Here we explore the endocrine regulation of sexual dimorphism in horned beetles. Specifically, we explore the role of juvenile hormone (JH) in regulating horn expression in females of two species with regular sexual dimorphism for pronotal horns (females have much shorter horns than males) and a third species with a rare reversed sexual dimorphism for both pronotal and head horns (females have much larger horns in both body regions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Furthermore, comparative morphological studies have shown that head and thoracic horns in the same species can differ widely in the degree to which their development is affected by sex and nutrition, suggesting that sex-and nutrition-dependent horn development can diversify independently for different body regions (21,23,24,27). Taken together, our results paint an extraordinarily dynamic picture of dsx evolution and its role in the origin and diversification of sexual and male dimorphism in horned beetles.…”
Section: Resultsmentioning
confidence: 57%
“…Furthermore, comparative morphological studies have shown that head and thoracic horns in the same species can differ widely in the degree to which their development is affected by sex and nutrition, suggesting that sex-and nutrition-dependent horn development can diversify independently for different body regions (21,23,24,27). Taken together, our results paint an extraordinarily dynamic picture of dsx evolution and its role in the origin and diversification of sexual and male dimorphism in horned beetles.…”
Section: Resultsmentioning
confidence: 57%
“…In addition, medium to high levels of the JH analog methoprene applied to the final instar of stalk-eyed flies results in a reduction or even a complete switch in the direction of SSD (from male-biased SSD to female-biased SSD) (63). Furthermore, several studies have shown that JH is important in creating dimorphism in beetle horns (42, 109). The results of these studies suggest that JH may play an important role in producing adult SSD, but the inconsistent results among studies indicate that much more work is needed before we will have an understanding of how and even if JH plays a role in producing SSD.…”
Section: Phenotypic Plasticity In Body Size In Insectsmentioning
confidence: 99%
“…33 and 45-47) by using a residual analysis as detailed in ref. 48. We used two-tailed T tests to determine whether horn length residuals differed significantly across treatment groups.…”
mentioning
confidence: 99%